Implicações das competências técnico-organizacionais para a performance competitiva em empresas seguidoras de mercado: evidências do segmento de turismo de aventura no Rio de Janeiro - Cavalcanti, Glauco dos Santos Scelza (2005)
This work focuses on the implications of technological-organizational competences for improvement of performance indicators. This relationship is examined during 1984 to 2005 in three small companies that operate in Rio de Janeiro within adventure tourism, more specifically, within tandem flights on hang-gliding. Based on a comparative case study grounded in both qualitative and quantitative empirical evidences collected in a detailed field search, this study is supported by an existing metric available in literature and adapted to adventure tourism segment. The metric to measure competences is based on four techno-organizational function: (i) product; (ii) sales & marketing; (iii) infra-structure & operational process; (iv) managing systems. The examination of performance improvement is based on a set of typical indicators used by this segment to evaluate results. This dissertation contributes to deepening the understanding of how techno-organizational competences affect the competitive performance of companies in this sector of adventure tourism.